“Silybum marianum” – properties and application in medicine – a review - Sowińska, Marta; Szpunar, Magdalena (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The subject of this article is milk thistle – a plant belonging to the Asteraceae family. Due to its properties, it has a beneficial effect on the functioning of important organs and systems of the human body. The aim of this paper was to review information on milk thistle, its use in medicine and the description of some of the chemical compounds due to which it owes its healing properties. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The article is a review of the publicly available literature on milk thistle, the chemical composition of its compounds and its use in medicine. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Current information about Silybum marianum is presented. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Milk thistle is a valuable medicinal plant due to the presence of numerous antioxidant and anti-inflammatory compounds. The benefits of supplementation with ingredients derived from milk thistle, their negligible interaction with other drugs and the lack of significant side effects, known so far, indicate that the plant described in the article can be a good medicine and a preventive measure against diseases affecting our society.